Implementation of The Madrasah Movement in Heart Towards a Culture if Achievement in Realizing The Profile of Pancasila Students at MAN 1 Jepara - Muhammad Andi Kurniawan; Tutik Wijayanti (Jurnal Civicus, 2023)
This research is motivated by the needs and challenges of the Industrial Revolution 4.0 which is accompanied by low attention to Education 4.0, the degradation of morality and character of the younger generation. Therefore, there is a need for system innovation and school cultural management as an effort to improve the quality of education as well as strengthen the character of the younger generation by implementing GEMATI towards a Culture of Achievement in realizing the Pancasila Student Profile at MAN 1 Jepara. This study uses a descriptive qualitative method with research locations in MAN 1 Jepara. Data collection was obtained through primary and secondary data sources, with data validity techniques through source and technique triangulation and using interactive data analysis models. The results of this study indicate GEMATI implementation planning towards a culture of achievement in realizing the Pancasila Student Profile begins with channelization and curriculum development and focusing on the basic concentration of ISL-based disciplines; learning formulation 4.0; implementation of Achievement Culture by cultivating 5 basic values in realizing the P5 dimension. GEMATI moves simultaneously to build Religious, Humanist, Smart, Innovative, and Competitive as a cultural foundation that mandates the essential function of realizing the P5 dimension. Evaluation management is carried out structurally top down and produces a structured pattern for monitoring, supervision and evaluation in the implementation of work plans.